Partial albinism in Rhinelepis aspera from the Upper Paraná Basin, Brazil,with a review of albinism in South American freshwater fishes - André Batista Nobile; Diogo Freitas-Souza; Felipe Pontieri de Lima; Aline Angelina Acosta; Reinaldo José Da Silva (Revista Mexicana de Biodiversidad)
This study reports a case of partial albinism in Rhinelepis aspera from the Aguapeí River, Upper Paraná Basin, Brazil and provides a review of albinism cases in freshwater fishes from South America. The captured specimen has depigmentation throughout almost its entire body, with pigmented eyes and little dark spots on the dorsal and caudal fins. It is an adult male, and we suggest that due to the benthic habitat, it would be able to reach adult size, avoiding predators. The review shows a scarcity of this phenomenon in nature.